Enhancing Ante Natal Care (ANC) Quality Through Interprofessional Collaboration (IPC) Among Health Workers - Miftahul Fikrah; Laila Isrona; Amirah Zatil Izzah (Lembaga Pengembangan Kinerja Dosen, 2024)
The increased of Maternal Mortality Rate (MMR) can be lowered through by various efforts, one of them with quality Antenatal Care (ANC). Quality of ANC services can be given by several health workers who work together in giving services to patients through the Interprofessional Collaboration (IPC). IPC or interprofessional collaboration can improve health service quality. The purpose of this study is to find out an overview of the level of perception of health workers about IPC on ANC services in Lubuk Buaya Health Center. This study is descriptive research using crosssectional design. The study sample is 30 health workers who are determined by the total sampling method. Data collection use the Collaborative Practice Assessment Tools (CPAT) questionnaire. The results of the study can be found that all health workers (100%) have a high perception of IPC in ANC services with components of connection among members, coordination and division of roles, and missions, goals, and objectives have the highest percentage (100%) and decision-making and conflict management components have the lowest percentage (10%). All health professions consist of GPs, midwives, nurses, dentists, pharmacists, nutritionists, and ATLM have a high perception (100%) of IPC on ANC services. The dentist professions have a high perception of all eight components, meanwhile other professions have a high perception of the seven components of perception and have a moderate perception in one component of perception, that is the components of decision making and conflict management. In general, health workers have a high perception of IPC in ANC services, but there are still a moderate perception in one components of perception so efforts are needed to improve IPC competence in that component.